Analisis Faktor-Faktor Pengambilan Keputusan Pemilihan Hutan Mangrove Pada Program MAGER (Mangrove Green Concert) Earth Hour Surabaya - Rania Hanin Sajida; Azeria Diazpitaloka Putri Sulistyono; Adam Jamal (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze decision-making factors in selecting mangrove forests in the MAGER program at Earth Hour Surabaya. This research method uses a qualitative descriptive approach with data collection techniques, namely interviews with five people related to decision making in selecting mangrove forests. The results of this research are that there are several factors in decision making at Earth Hour Surabaya seen from a person's position in making decisions, problems, situations, conditions and goals in making these decisions. In making decisions regarding this phenomenon, the decisions taken have gone through several processes that consider various things so that the decision can be taken.